Inovação e Benchmarking: Uma Parceria Eficiente? - Carvalho, Luísa Margarida Cagica; Reis, Henrique Manuel Pimentel (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2006)
Contemporary life implies developing business activity in an increasing competitive environment and constant focus on organizations efficiency Innovation is a relevant key factor for companies aiming defeating competitors and getting stronger in market. We begin for framing this concept accordingly to the most known authors, and then we explain the main innovation types and its characteristics, relieving those we consider important in this work. Later on we broach and explain benchmarking, its importance as management tool and the different typologies for its application. We close this cycle linking this tool with innovation management, relieving the aspects of using the former that make easier the management of the latter. We broach in a synthetical way the link between strategic benchmarking and innovation management, and we finish with our conclusions about benchmarking and innovation partnership efficiency.